Modelling the initiation of bitumen-filled microfractures in immature, organic-rich carbonate mudrocks: The Maastrichtian source rocks of Jordan. (July 2022) - Abu-Mahfouz, Israa S.; Wicaksono, Akbar N.; Idiz, Erdem; Cartwright, Joe; Santamarina, J. Carlos; Vahrenkamp, Volker C.
Abstract: The initiation of bitumen-filled microfractures was analysed in the organic-rich Maastrichtian carbonate mudrocks of Jordan, which show great potential as source rocks and for a future unconventional hydrocarbon play. A modelling approach was performed to assess the possible scenarios causing horizontal small-scale (mm to cm in length) bitumen fractures (microfractures) at the immature stage. The aim was to back-calculate how much overpressure and bitumen generation was needed in the past to initiate horizontal microfracturing, comparing those simulated parameters with the actual generation potential from the source rock samples. The results show that the local overpressure resulting from the bitumen generation during early catagenesis was not high enough to initiate the microfracturing. We hypothesise that the increase of internal pressure was caused by the inability of the bitumen to be squeezed into the pore space during burial. The resulting overpressure induced a perturbation to the stable-state stress distribution around the kerogen boundary that eventually led to the initiation of horizontal microfractures along the tip of bitumen flakes. Subsequently, short-distance migration of bitumen and a significant decrease in pressure have prevailed in the study area. This proves that primary migration can occur long before the source rock reaches the oil or gas windows, at a comparatively shallow burial depth. This also indicates that the first framework pathways by the precursor horizontal microfractures may control the flow patterns of the hydrocarbons within source rocks. Understanding these factors is critical to predicting the impact of these microscale fractures on hydrocarbon expulsion and storage, and hence likely productivity of an analogous subsurface unconventional reservoir. Highlights: Bitumen expulsion can occur at the earliest stages of kerogen cracking (maturation). Original kerogen shape influences the orientation of microfracturing (the direction of initiation and propagation). Horizontal micro-fractures control the flow patterns of the hydrocarbons within the source rock. The increase of internal pressure is caused by the inability of the bitumen to be squeezed into the pore space during burial.